Pendampingan Pembelajaran Baca Tulis Al-Quran dan Penulisan Pegon di TPQ Al-Kautsar Desa Sumokembangsri - Maulidia Ilham Fadilah; Nurul Arifin; Muhammad Sultan Sahputra; Eli Masnawati; Masfufah Masfufah; Yuliastutik Yuliastutik; Siti Kholidatur Rodiyah; Nelud Darajaatul Aliyah; Mila Hariani (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
This study aims to evaluate the effectiveness of assistance in teaching Quran reading and writing as well as Pegon script at Taman Pendidikan Qur'an (TPQ) Al-Kautsar, Sumokembangsri Village. The assistance is designed to enhance students' skills in reading and writing the Quran, as well as in Pegon script, which is part of the local tradition. The method used in this community service program employs Participatory Rural Appraisal, involving field surveys and direct communication with the community. The results indicate that routine and structured assistance significantly improves students' abilities in reading the Quran and writing Pegon script. The program also positively impacts students' understanding and skills in effectively practicing both aspects. This community service program is expected to contribute to the development of better and more adaptive teaching methods at TPQ and strengthen the preservation of local culture through Pegon script writing.